Virtual reality video project design to improve vocational teachers' skills in implementing Kurikulum Merdeka - Yana Endrayanto; Yudi Sukmayadi; Juju Masunah (Universitas Negeri Yogyakarta, 2023)
This project aims to improve the skills of vocational teachers in implementing the Merdeka Curriculum, with the design of the Merdeka Curriculum virtual reality video project to encourage the use of a learner-centered approach and prioritize skills-based learning relevant to the world of work. VR video content is designed to improve vocational teachers' understanding and skills in implementing the Merdeka Kurikulum. The purpose of this research is to facilitate teachers to have pedagogical skills in preparing teaching materials to evaluate learning. The method in this research is Action research with the VR video content development process involving determining clear learning objectives, designing a VR curriculum, preparing VR materials and content, and making VR videos using relevant technology and software. Furthermore, VR video content is implemented in vocational teacher learning by providing access to VR devices and clear usage guidelines. Evaluation is conducted to measure the effectiveness of VR videos in achieving learning objectives and obtain feedback from vocational teachers. The results of this project show that using VR videos in vocational teachers' learning can improve their engagement, understanding, and skills in the context of the Merdeka Curriculum. Vocational teachers experience a more interactive and immersive learning experience through a realistic virtual environment. Students also benefit from using VR videos, with an increased understanding of vocational concepts and their readiness for the world of work. The project also faced some challenges, such as the accessibility of VR devices and technical constraints. In discussing the project results, it is recommended to collaborate with related parties and share experiences with the education community so that the use of VR videos in vocational learning can expand and continue to grow.